Les pratiques langagières en milieu commercial : étude sociolinguistique réalisée au marché hebdomadaire « El Hamri » à Oran » - Chernouhi, Ahmed (Journal of Ecohumanism, 2026)
In this study, we aim to examine the language practices of speakers at the “El Hamri” weekly market in Oran from an urban sociolinguistic perspective. In doing so, we seek to highlight language practices in an urban commercial setting, a place where speakers of varying educational backgrounds and using diverse forms of communication come together. In line with this, we plan to develop a sample of data for a sociolinguistic study of language use at the weekly market, examining the patterns of verbal interaction among speakers within an informal trading environment. This research aims to re-examine the key characteristics of speakers’ linguistic repertoires in situations of spontaneous communication and within the context of commercial practices. Similarly, we aim to highlight the discursive output of speakers in the marketplace whilst situating ourselves within the theoretical and methodological frameworks of the field of urban sociolinguistics developed by researchers from various academic backgrounds, such as: Bulot and Veschambre (2006), Calvet (1994), Caubet (2004), Drivaud and Peretz-Juillard (1984), Lindenfeld (1985), Sopylyuk (2017), Abdelhamid and Cherak (2019), Taleb-Ibrahimi (1997), (2000) and (2002). Furthermore, this fieldwork is based primarily on the collection of data relating to the language practices and speech of those involved in the “El Hamri” weekly market. We have, in fact, employed two methods of data collection: the first involves recordings made using a tape recorder. As for the second, we conducted interviews with respondents aged between 19 and 56, comprising two groups: traders and visitors. The recording process enabled us to collect speech sequences, each consisting of numerous turns of speech, whilst excluding non-significant sounds, background noise and moments of interruption. It should be noted that this study is both a macrosociolinguistic study (involving questionnaires and interviews) and a microsociolinguistic study (analysing language use). From the outset, this monograph aims to demonstrate how speakers (traders and customers) at the weekly market employ language characterised by linguistic devices in general, and lexical ones in particular, which give rise to innovative forms of expression. Furthermore, it seeks to identify the linguistic phenomena emerging within their language(s).